Association between ethylene oxide exposure and osteoarthritis risk: an analysis of NHANES data (2013–2014 and 2017–2018) - Li, Zhongshan; Qu, Qi; Wang, Zhiyu; Mou, Shuanglin; Jiang, Rui; Zhu, Wensheng (Frontiers in Public Health, 2025)
BackgroundEthylene oxide (EO) is widely used as a disinfectant and is also a common environmental pollutant. Exposure to EO has been associated with various systemic diseases, posing crucial health risks. However, EO is frequently employed as a sterilizing agent in orthopedics, while its association with the risk of skeletal system diseases remains insufficiently evaluated. This study aims to investigate the association between EO exposure and the risk of Osteoarthritis (OA), a prevalent orthopedic condition.MethodsA total of 3,386 participants were selected from the National Health and Nutrition Examination Survey (NHANES) 2013–2014 and 2017–2018 cycles, including 952 individuals with OA. Box plots assessed EO concentration differences between OA and non-OA groups. Weighted logistic regression models and restricted cubic spline (RCS) models were used to evaluate the relationship between EO exposure and OA risk. Subgroup analysis and interaction test explored variations in the association across different characteristics.ResultsNo significant difference in EO concentrations was found between OA and non-OA groups. In multivariate logistic regression, high EO level exposure was significantly associated with increased OA risk. Additionally, a nonlinear U-shaped and J-shaped association was observed in the unadjusted and adjusted RCS models, respectively. Subgroup analysis revealed that the association between EO exposure and OA risk was more pronounced in the 20–40 and 40–65 age groups, never smokers (Not at all), and those with low calcium levels (< 8.5 mg/dL) or low vitamin D levels (< 75 nmol/L).ConclusionsEO exposure is associated with OA risk, exhibiting a J-shaped relationship, with this association being particularly pronounced in individuals under 65 years old or those with low calcium or vitamin D levels. Further prospective studies are needed to examine the association between EO exposure and OA risk.